PROBLEMATIKA PENERJEMAAH ANTAR BAHASA DALAM ILMU AL-DILALAH - Abdullah Husen; Wahyu Wahyu; Muhammad Fadhilah Akbari (Universitas Islam Negeri Mataram, 2023)
This study aims to analyze the essential challenges and problems in translating scientific texts based on Al-Dilālah (semantics) into a target language. The primary focus of this research is to explore the linguistic and cultural barriers that arise when transferring technical meanings from the linguistic scholarly tradition into a global context. The research employs a descriptive qualitative method with a literature review approach, where data were collected through an examination of Al-Dilālah scientific documents and analyzed using content analysis techniques to map existing translation issues. The findings indicate that the primary complexities lie in precise word choice, structural adjustments, and interpretive dilemmas related to historical-cultural meanings. As a solution, this study formulates strategies involving translators who possess a profound understanding of the source culture to maintain the accuracy and integrity of the original meaning. These findings are expected to contribute to the development of more effective and accurate translation methods for scholarly texts rooted in linguistic sciences.